The relationship between teamwork, moral sensitivity, and missed nursing care in intensive care unit nurses - Monir Nobahar; Malihe Ameri; Shahrbanoo Goli (BMC, 2023)
Abstract Background Teamwork, moral sensitivity, and missed nursing care are important healthcare challenges for Intensive Care Unit (ICU) nurses and the existence of a relationship between these variables can be useful for developing better care improvement strategies. This study aimed to determine the relationship between teamwork, moral sensitivity, and missed nursing care in ICU nurses. Methods This is a descriptive cross-sectional study conducted on a total of 200 ICU nurses working at teaching hospitals affiliated to Semnan and Shahroud Universities of Medical Sciences, Semnan, Iran in 2022. Sampling was conducted using the census method. Data collection was conducted using a demographic checklist, the TeamSTEPPS Team Perception Questionnaire (T-TPQ), Lützén Moral Sensitivity Questionnaire (L-MSQ), and Kalisch and Williams Missed Nursing Care (MISSCARE) Survey. The examination of the relationship between the three variables was conducted using Pearson's correlation coefficient and multiple regression analysis. Results The mean and standard deviation of teamwork, moral sensitivity, and missed nursing care was 3.47 ± 0.69, 64.19 ± 13.43, and 55.04 ± 34.10, respectively. The variable of teamwork had a significant positive relationship with moral sensitivity (p < .001) and a significant negative relationship with missed nursing care (p < .001). Teamwork was also a positive predictor of moral sensitivity (p < .001) and a negative predictor of missed nursing care (p < .001). The clinical experience of ICU nurses was a positive predictor of teamwork (p = .01) and a negative predictor of missed nursing care (p = .001). The age of ICU nurses was a positive predictor of moral sensitivity (p = .001) and a negative predictor of missed nursing care (p = .008). Conclusion The findings showed that a higher level of teamwork was associated with increased moral sensitivity and reduced missed nursing care among ICU nurses. Therefore, focusing on planning interventions on teamwork improvement can lead ICU nurses to improve moral sensitivity, lower missed nursing care, and promote the quality of patient care.